NEW SEMIORGANIC IODINE COMPLEX, ITS STRUCTURE AND BIOLOGICAL ACTIVITY - N.A. Paretskaya; R.A. Tamazyan; N.B. Akhmatullina; A. Amanzholkyzy; A.N. Sabitov; S.B. Berdіbai; B.F. Kerimzhanova; A.B. Dzhumagazieva; I.S. Korotetskii; A.I. Ilin (Academic Scientific Journal of Chemistry, 2019)
The crystal structure of a new coordination compound formed in the tryptophan:NaI:iodine system was examined, and unit cell parameters were determined. A chemical structure of the compound was determined by X-ray diffraction analysis as C11H12N2O2•(C11H13N2O2) + •Na+ •2Н2О • (I4) 2-. The coordination compound showed low toxicity and exhibited bactericidal activity against both susceptible and multiresistant strains of bacteria S. aureus, P. aeruginosa, and E. coli.